Mg < 2 + >-assisted collagen DLP 3D printing bio-ink, and preparation method and application thereof

Through the MG2+auxiliary cross -linking technology, a collagen DLP 3D printing biological ink with high biological activity and mechanical properties has been developed, which solves the problem of lack of water -soluble and mechanical strength of collagen in DLP 3D biological printing technology. Wide application in the field of biomedical.

CN119367603APending Publication Date: 2025-01-28GANSU SKYLINE BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410622482.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the existing DLP 3D bioprinting technology, collagen is difficult to meet the needs of biomedical applications due to its poor water solubility and limited mechanical strength. At the same time, traditional chemical crosslinking agents may cause harmful residues and affect clinical applications.

Method used

Using MG2+as an cross -linked agent for collagen, collagen biomas with high biological activity and mechanical properties through MG2+auxiliary cross -linking, combined with methyl acrylic acidized collagen, light cause and ultraviolet absorbent to prepare to prepare in blue light irradiation Under the rapid curing biological ink.

Benefits of technology

Realize the high current and rapid solidification of collagen biological ink, improve the mechanical strength and antidase degradation capacity of 3D printed stents, significantly promote the proliferation, migration and differentiation of cells, accelerate the orderly deposition and epidermis of collagen It is suitable for skin repair, osteo cartilage repair, and organizational engineering fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367603A_ABST
    Figure CN119367603A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biology, and particularly relates to a preparation method and application of Mg < 2 + >-assisted collagen DLP 3D printing bio-ink, and the bio-ink comprises the following components: 0.5%-1% m / v of methacrylic acid collagen, 0.1%-0.5% m / v of a photoinitiator, 0.1%-0.5% m / v of an ultraviolet absorbent and 0.1%-0.5% m / v of Mg < 2 + >. The bio-ink has good flowability and is rapidly cured under blue light irradiation, and DLP 3D precise printing of collagen is achieved; the 3D printing stent is high in mechanical strength and high in enzymatic degradation resistance; the 3D collagen biological scaffold has high biocompatibility and biological activity, and cell proliferation, migration and differentiation are remarkably promoted; the 3D printing biological scaffold can promote ordered deposition of collagen and accelerate epidermis regeneration; the 3D printing biological scaffold is widely applied to the fields of skin repair and osteochondral repair tissue engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biotechnology and specifically relates to a Mg 2+ Assisted collagen DLP 3D printing bio-ink, preparation method and application. Background Art

[0002] 3D bioprinting is a rapid prototyping technology based on customized three-dimensional models. It uses computer-aided design and numerical control systems to accurately position and assemble biomaterials. It is widely used in the production of biological scaffolds, tissues, organs, and medical auxiliary equipment. 3D printing technology has the characteristics of being fast, accurate, personalized, differentiated, and particularly suitable for manufacturing complex-shaped entities. It has attracted much attention in the fields of regenerative medicine and tissue engineering. At present, inkjet and extrusion 3D bioprinting have been used to manufacture personalized structures. However, inkjet bioprinting is prone to nozzle clogging due to the use of high-viscosity materials; while extrusion bioprinting takes a long time and lacks printing accuracy. Digital Light Processing (DLP) bioprinting technology is increasingly widely used in disease modeling and regenerative medicine due to its advantages such as fast speed, high precision, and no nozzle clogging.

[0003] The preparation of bio-ink is the core link in DLP 3D bioprinting technology. When this type of ink is used to manufacture medical materials, it must meet the following strict conditions: (1) Printability: It should be able to precisely control additive molding in spatial and temporal dimensions and must solidify quickly; (2) Biocompatibility: Ensure that the printed medical materials have excellent biocompatibility; (3) Mechanical stability: The material should exhibit long-lasting mechanical properties; (4) Degradability: The material needs to have biodegradability; (5) Bionics: It should simulate the functions of natural biological tissues. At present, gelatin is a widely used bio-ink component and is mentioned in multiple invention patents such as CN202310232743.0. The formula includes methacryloyl gelatin, polyethylene glycol diacrylate, cellulase, Lactobacillus pentosus and liquid culture medium. However, gelatin destroys the unique triple helix structure of collagen, resulting in a significant reduction in biological activity, which seriously limits its biomedical application. Therefore, the development of a new type of highly bioactive bio-ink is crucial to promote the application of DLP 3D bioprinting technology.

[0004] As the most abundant protein in the human body, collagen constitutes the main part of the extracellular matrix and provides structural support for a variety of tissues and organs. Thanks to its excellent biological activity, low immunogenicity and excellent biodegradability, collagen has been widely used in the field of tissue engineering. However, in the application of DLP 3D printing technology, collagen faces challenges caused by its poor water solubility and limited mechanical strength. Currently, the printing method of methacrylated collagen combined with chemical crosslinkers is used to enhance structural strength, but this method may result in harmful chemical crosslinker residues, seriously affecting its clinical application prospects.

[0005] The inventor unexpectedly discovered during the research that Mg 2+ It can be used as an effective collagen cross-linking agent to significantly enhance the mechanical properties and thermal stability of collagen. Magnesium is an essential trace element for the human body. It is known to play a key role in protein synthesis, enzyme activity regulation, muscle contraction, nerve transmission, and bone health maintenance. It is also an indispensable element for maintaining normal metabolic function. 2+ The collagen bio-ink obtained by cross-linking has good fluidity and quickly solidifies under blue light irradiation, and can be used to prepare DLP 3D precision printed collagen scaffolds. The collagen 3D scaffold not only exhibits good mechanical properties and fidelity, but also has low water absorption and enhanced anti-degradation ability; at the same time, it has excellent biological activity, can significantly promote cell adhesion, proliferation, migration and differentiation, accelerate the orderly deposition of collagen and epidermal regeneration, thereby accelerating tissue repair. Therefore, Mg 2+ Cross-linked collagen DLP 3D printing bio-ink has broad application potential in tissue engineering and biomedicine. Summary of the invention

[0006] In view of the above technical problems, the primary purpose of the present invention is to provide a Mg 2+ DLP 3D printing bio-ink for collagen, the bio-ink comprising the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ Solution.

[0007] Preferably, the collagen is yak collagen.

[0008] Preferably, the yak collagen is type I yak collagen, and / or type II yak collagen, and / or type II yak collagen.

[0009] Preferably, the photoinitiator includes one or more of LAP, TPO, and I2959.

[0010] Preferably, the photoinitiator is LAP.

[0011] Preferably, the ultraviolet absorber includes one or more of lemon yellow and food coloring brilliant blue.

[0012] Preferably, the ultraviolet absorber is lemon yellow.

[0013] The second object of the present invention is to provide a method for preparing the bio-ink, comprising the following steps:

[0014] (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve;

[0015] (2) adding sodium hydroxide solution to adjust the pH of the collagen solution obtained in step (1) to 7-9, then adding methacrylic anhydride (MA) dropwise, and maintaining the pH of the solution at 7-8; reacting in an ice bath for 24 hours, dialyzing in ultrapure water, and freeze-drying to obtain methacrylated collagen (CMA);

[0016] (3) Prepare 0.5% to 1% m / v methacrylated collagen solution with 0.5M acetic acid solution, add 6M sodium hydroxide solution to adjust the pH of the solution to neutral, add 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ The solution was mixed evenly and centrifuged to remove bubbles to obtain CMA-Mg 2+ Bio-ink.

[0017] Preferably, the amount of methacrylic anhydride added in step (2) is ten times the equivalent of collagen lysine.

[0018] The third object of the present invention is to provide a method for preparing a 3D printing functional active material, comprising: adding biological ink to a 3D bioprinter for printing, and then performing photocrosslinking to obtain a 3D printing functional active material, wherein the biological ink is the biological ink or the biological ink prepared by the preparation method.

[0019] The fourth object of the present invention is to provide a 3D printing functional active material, which is obtained by sequentially subjecting the biological ink or the biological ink prepared by the preparation method to 3D printing and cross-linking treatment.

[0020] The fifth object of the present invention is to provide the application of the 3D printing functional active material in the preparation of skin repair materials, bone cartilage repair materials, and tissue engineering.

[0021] The beneficial effects of the present invention are: the present invention provides a Mg 2+DLP 3D printing bio-ink for collagen, the bio-ink comprising the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ solution; the bio-ink has good fluidity and can be quickly solidified under blue light irradiation to achieve DLP 3D precision printing of CMA; the 3D printed scaffold has high mechanical strength and strong resistance to enzyme degradation; the 3D collagen bio-scaffold has high biocompatibility and bioactivity, and significantly promotes cell proliferation, migration and differentiation; the 3D printed bio-scaffold can promote the orderly deposition of collagen and accelerate epidermal regeneration; 3D printed bio-scaffolds are widely used in the fields of skin repair and bone and cartilage repair tissue engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Methacryloyl Collagen-Metal Ion Solution

[0023] Note: (A) CMA-Al 3+ ; (B) CMA-Cu 2+ ; (C) CMA-Mg 2+ ; (D) CMA-Ca 2+ .

[0024] Figure 2 Characterization of methacryloyl-collagen-magnesium (CMA-Mg) bioink Note: (A) Viscosity test of CMA, CMA-Mg1 and CMA-Mg2 bioinks; (B) Storage modulus and loss modulus of CMA, CMA-Mg1 and CMA-Mg2 bioinks after in-situ curing; (C) Maximum storage modulus of CMA, CMA-Mg1 and CMA-Mg2 bioinks after in-situ curing; (D) CAD drawing of DLP 3D printing of CMA-Mg2 bioink.

[0025] Figure 3 Characterization of the properties of DLP3D printed collagen scaffolds Note: (A) Cyclic compression test of CMA, CMA-Mg1, and CMA-Mg2 scaffolds; (B) Stress-strain curves of CMA, CMA-Mg1, and CMA-Mg2 hydrogels; (C) Strain oscillation rheology of CMA, CMA-Mg1, and CMA-Mg2; (D) Young's modulus of CMA, CMA-Mg1, and CMA-Mg2 hydrogels; (E) Uniaxial compression fracture energy of CMA, CMA-Mg1, and CMA-Mg2 hydrogels; (F) Average pore size of CMA and CMA-Mg hydrogels; (G) DSC analysis of CMA, CMA-Mg1, and CMA-Mg2 hydrogels; (H) Swelling properties of CMA, CMA-Mg1, and CMA-Mg2 scaffolds; (I) Resistance of CMA and CMA-Mg hydrogels to enzymatic degradation.

[0026] Figure 4 In vitro biocompatibility and bioactivity of collagen hydrogels.

[0027] Note: (A) Live / dead cell staining of L929 cells encapsulated in CMA, CMA-Mg1, and CMA-Mg2 hydrogels after 1, 5, and 8 days of culture; (B) Live cell counts of L929 cells encapsulated in CMA, CMA-Mg1, and CMA-Mg2 hydrogels after 1, 5, and 8 days of culture; (C) Top view of 3D imaging of cells incubated on CMA-Mg2 scaffolds for 8 days; (D) Side view of 3D imaging of cells incubated on CMA-Mg2 scaffolds for 8 days; (E) L929 cells were encapsulated in CMA-Mg2 bioink and printed into pentagonal, peach, and grid-like structures.

[0028] Figure 5 Collagen bioscaffolds have good bioactivity Note: (A) CLSM images of BMSCs on scaffold materials, phalloidin staining of F-actin (red) and 33258 staining of cell nuclei (blue); (B) Cell migration; (C) Cell migration rate; (D) Relative expression level of Sox9; (E) Relative expression level of Col2a1

[0029] Figure 6 CMA-Mg hydrogel promotes skin wound repair.

[0030] Note: (A) Photo of wound healing; (B) Schematic diagram of skin wound changes over time; (C) Skin wound closure rate

[0031] Figure 7 CMA-Mg hydrogel promotes wound repair Tissue staining Note: (A) H&E; (B) Masson staining; (C) granulation tissue; (D) epidermal regeneration; (E) collagen deposition DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the specification. Obviously, the described embodiments are only a part of the present invention, not the whole of the invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the following examples, unless otherwise specified, the methods used are all conventional methods;

[0034] In the following examples, unless otherwise specified, the reagents used are conventional reagents and can be purchased from the market.

[0035] In the following examples, the collagen used was extracted by our laboratory. The extraction method is described in invention patent CN113520900B.

[0036] Example 1 Methacrylylated collagen-metal ion solution

[0037] Dissolve the freeze-dried collagen sponge in 0.5M acetic acid solution to prepare a 0.3% m / v collagen solution, slowly stir and dissolve to form a uniform solution. After adding 6M sodium hydroxide solution to adjust the pH of the collagen solution to 7-9, add 10 times the equivalent of methacrylic anhydride (MA) of collagen lysine, and keep the solution pH at 7-8. After reacting in an ice bath for 24 hours, dialyze in ultrapure water for 4 days, freeze-dry, and prepare methacrylylated collagen (CMA).

[0038] Dissolve CMA in 0.5M acetic acid solution to prepare a 0.5% m / v solution, add sodium hydroxide solution to adjust the pH to neutral, and add 0.5% m / v Al 3+ , Cu 2+ , Ca 2+ and Mg 2+ solution to obtain a methacrylylated collagen-metal ion solution.

[0039] The experimental results are as follows Figure 1 As shown, adding Al 3+ , Cu 2+ and Ca 2+ The methacryloyl collagen-metal ion solution gelled quickly and unevenly, and could not be used as a bio-ink. 2+ The solution viscosity in the group increased, but it still maintained fluidity and could be used as a bio-ink. Therefore, in subsequent experiments, we chose Mg 2+ solution as a cross-linking agent.

[0040] Example 2 Preparation of biological ink CMA-Mg 2+

[0041] The bio-ink includes CMA solution, photoinitiator LAP, UV absorber UA and Mg 2+ 4 solutions. Prepare CMA-Mg according to Table 1 2+ Bio-ink. Among them, in bio-inks 1, 2, 3 and 4, CMA forms a uniform solution but cannot form a gel; in bio-inks 5, 6, 7 and 8, CMA forms a uniform solution with high printing precision, but bio-ink 7 requires a long printing time, bio-ink 8 has a fast printing speed and low precision, and high concentrations of LAP may be cytotoxic; in bio-inks 9, 10, 11 and 12, CMA has low solubility, high viscosity and low printing precision. Therefore, we selected bio-inks 5 and 6 for subsequent experiments.

[0042] Table 1 Content of each component in different bio-inks

[0043]

[0044] Example 3 Characterization of Methacrylylated Collagen-Magnesium (CMA-Mg) Bio-Ink

[0045] By comparing 0.5% m / v CMA bioink and CMA-Mg 2+ Viscosity test of bio-ink 5 and 6. We studied Mg 2+ Effect of Mg on the fluidity of collagen bio-ink. When the shear rate is low, the viscosity of the collagen ink increases with the increase of Mg 2+ The concentration increases; when the shear rate increases to 1s -1 When CMA bio-ink and CMA-Mg 2+ The viscosities of bio-inks 5 and 6 are similar ( Figure 2 A). The results show that magnesium ions do not affect the viscosity of CMA ink.

[0046] Through rheological properties testing, we investigated the CMA bio-ink and CMA-Mg 2+ Rheological properties of bio-inks 5 and 6 during UV curing. Before irradiation, CMA bio-ink and CMA-Mg 2+ Bio-inks 5 and 6 behave as stable liquids with constant storage modulus (G') and loss modulus (G'). 2 Under the irradiation of blue light, the storage modulus increases rapidly and is higher than the loss modulus, showing the hydrogel characteristics ( Figure 2 B) CMA bio-ink and CMA-Mg 2+ The storage moduli of bio-inks 5 and 6 are 400Pa, 680Pa and 760Pa respectively. Figure 2 C), where CMA-Mg 2+ The storage modulus of bio-ink 5 is much higher than that of CMA. The results show that magnesium ions can enhance the storage modulus of CMA ink after curing, which is beneficial to the DLP 3D printing of CMA.

[0047] Example 4Mg 2+ Assisted collagen DLP precision 3D printing

[0048] We designed CAD models of complex bionic structures such as tubular, meniscus, and ear for DLP printing to verify the CMA-Mg 2+ Printing performance of bio-ink 5 ( Figure 2 D) CMA-Mg 2+Bio-ink 5 was added to the DLP 3D printer and printed under the conditions of slice thickness of 100 μm, base exposure time of 17 s, and slice exposure time of 14 s. All printed hydrogels showed the same shape characteristics as the originally designed CAD model, indicating that CMA-Mg 2+ Bio-ink 5 has good printability. The results show that CMA-Mg 2+ Bio-ink 5 enables high-precision printing of a variety of models.

[0049] Example 5 CMA-Mg 2+ Performance test of the bracket

[0050] We evaluated the mechanical properties of the 3D collagen scaffolds by cyclic compression tests. When the strain was 30%, the stresses on CMA, CMA-Mg1, and CMA-Mg2 were 15 kPa, 17 kPa, and 27 kPa, respectively. Figure 3 A). During the compression cycle, the absorbed energy of CMA, CMA-Mg1 and CMA-Mg2 is 54.14 kJ / m 3 、78.00kJ / m 3 and 151.60 kJ / m 3 , and the dissipated energy is 1.44 kJ / m 3 5.11kJ / m 3 and 22.78 kJ / m 3 The results showed that CMA-Mg2 had higher mechanical strength than CMA-Mg1 and CMA.

[0051] The compressive strength of the scaffold material was evaluated by uniaxial compression test. The stress-strain curve showed that the ultimate fracture strength (UFS) of CMA at a strain of 37.38% was 21.67 kPa; while the UFS of CMA-Mg1 at a strain of 34.17% was 27.01 kPa; and the UFS of CMA-Mg2 at a strain of 33.11% was 34.70 kPa ( Figure 3 B). The Young's moduli of CMA, CMA-Mg1 and CMA-Mg2 are 3.19 kPa, 6.04 kPa and 10.17 kPa respectively ( Figure 3 D). In addition, the fracture energies of CMA, CMA-Mg1, and CMA-Mg2 hydrogels were 135.64 kJ / m 3 、160.98kJ / m 3 and 221.77 kJ / m 3 ( Figure 3 E) These results further indicate that Mg 2+ Improved the mechanical properties of CMA-Mg hydrogel.

[0052] Strain-dependent oscillatory rheology showed that the G′ values ​​of CMA, CMA-Mg1, and CMA-Mg2 hydrogels remained unchanged within the linear viscoelastic region (LVR), showing solid-like viscoelastic characteristics ( Figure 3 C). It is worth noting that the G′ value of CMA-Mg2 hydrogel is 3.14 and 2.34 times that of CMA and CMA-Mg1 hydrogels, respectively, indicating that Mg 2+ The mechanical strength of CMA-Mg hydrogel was significantly enhanced through coordination with CMA.

[0053] The morphology of the hydrogels was analyzed using scanning electron microscopy (SEM). The SEM images of CMA and CMA-Mg hydrogels showed that CMA and CMA-Mg hydrogels had well-organized pore networks with average pore sizes of 107.28 μm and 79.82 μm, respectively. Figure 3 F) These results show that Mg 2+ Effectively promotes collagen cross-linking.

[0054] The thermal stability of CMA-Mg hydrogel was studied by differential scanning calorimetry (DSC). Figure 3 G). The results show that the thermal transition temperature of CMA is about 88.8℃, which is much higher than the thermal transition temperature of collagen (Col) of 56.8℃. The thermal transition temperatures of CMA-Mg1 and CMA-Mg2 are 94.3℃ and 103.5℃, respectively, both higher than CMA. 2+ Improved the thermal stability of CMA.

[0055] The CMA and CMA-Mg scaffolds were immersed in a solution containing 5 U / mL collagenase, and the ability of the scaffold materials to resist collagenase degradation was investigated. Figure 3 H). After 12 h, the degradation rates of CMA and CMA-Mg were 42.86% and 20.61%, respectively. After 11 days, the degradation rates of CMA and CMA-Mg were 86.24% and 67.88%, respectively, indicating that the CMA-Mg scaffold has a higher resistance to enzyme degradation. In vitro enzyme degradation experiments further showed that Mg 2+ Through coordination and cross-linking with CMA, the ability of CMA to resist enzyme degradation is enhanced.

[0056] We evaluated the stability of CMA, CMA-Mg1, and CMA-Mg2 scaffolds in solution by swelling ratio (SR) test. Figure 3I). At 56 min, the SR of CMA, CMA-Mg1, and CMA-Mg2 scaffolds increased rapidly, reaching 119.00, 109.60, and 98.47, respectively. CMA and CMA-Mg1 reached equilibrium within 216 min, with SRs of approximately 140 and 130, respectively. However, CMA-Mg2 reached equilibrium at 456 min, with SR of approximately 112. This indicates that CMA-Mg2 has a lower swelling rate. The swelling results show that Mg 2+ The swelling rate of collagen scaffold material was reduced.

[0057] Example 6 CMA-Mg 2+ Biocompatibility and bioactivity of inks

[0058] Detection of CMA-Mg by live-dead cell staining 2+ Biocompatibility of ink. 100 μL L929 cell suspension (1×10 6 cells / mL) and shake quickly. Pipette 250μL of cell-containing bio-ink and evenly add it to the confocal dish, and place it on a 405nm UV lamp for curing for 30s. Immediately after curing, wash with complete culture medium (DMEM, 5% FBS, 1% double antibody) three times. Add 2mL of complete culture medium and place it in a 37℃ incubator for culture. Change the culture medium every day, and remove it on the 1st, 5th and 8th days to remove the culture medium. First wash with 1×ABbuffer for 5min, add calcein (live cell staining) and PI (dead cell staining) according to the instructions, and stain at 37℃ for 1h in the dark. Use a laser confocal microscope to capture images.

[0059] The biocompatibility of collagen ink was evaluated by the proliferation of L929 cells in collagen hydrogels. Figure 4 ). Live / dead cell staining fluorescence images showed that as the incubation time increased, the number of L929 cells encapsulated in CMA, CMA-Mg1, and CMA-Mg2 hydrogels increased, indicating that the three hydrogels have a significant ability to promote cell proliferation ( Figure 4 A). ImageJ cell counting results further showed that the density of L929 cells encapsulated in CMA-Mg2 hydrogel was the highest, indicating that CMA-Mg2 has the best effect in promoting L929 proliferation ( Figure 4 B). The front and side views of the live / dead cell staining 3D imaging of L929 cells incubated on the CMA-Mg2 scaffold for 8 days show that L929 cells are evenly distributed in the hydrogel and the cells are in good growth condition ( Figure 4 C, D). These results indicate that CMA-Mg2 hydrogel has excellent biological activity and significantly promotes cell proliferation.

[0060] In addition, we further investigated the bioactivity of CMA-Mg2 hydrogel by cell-loaded DLP 3D printing. CMA-Mg2 was mixed with L929 cells to prepare bio-ink, and DLP bioprinted pentagonal, peach, and grid patterns ( Figure 4 EG). After 24 h of culture, live / dead cell staining fluorescence images showed that L929 cells were evenly distributed in the CMA-Mg hydrogel. These results show that CMA-Mg2 bio-ink loaded cell DLP bioprinting materials have high cell survival rate and printing accuracy, and have broad application prospects in the field of tissue repair.

[0061] We observed the adhesion and spreading characteristics of BMSCs on CMA and CMA-Mg hydrogel substrates using fluorescence confocal microscopy. Figure 5 A). Fluorescence images show that the number of cells in the blank group is small and the cells are cubic in shape. The cells on CMA and CMA-Mg hydrogels are slender spindles. Cell adhesion and spreading indicate that CMA-Mg hydrogel has a good ability to promote cell adhesion.

[0062] The effect of collagen bio-ink on cell migration ability was evaluated by cell scratch assay ( Figure 5 B, C). Microscope images show that after 0h of scratching, obvious scratch areas were visible in the blank group, CMA group and CMA-Mg group. After 24h of cell culture, only a small number of cells migrated in the blank group, while a large number of cells migrated to the scratch area in the CMA and CMA-Mg hydrogel groups. Among them, the CMA-Mg hydrogel group had the best scratch area closure effect ( Figure 5 B). The cell migration rate of the CMA-Mg group was 69.81%, which was significantly higher than that of the blank group (30.03%) and the CMA group (44.8%). These results indicate that CMA-Mg hydrogel can significantly promote cell migration.

[0063] The ability of collagen hydrogel to promote BMSCs differentiation was investigated by detecting the expression of collagen type II α1 chain (Col2a1) and SRY-box transcription factor 9 (Sox9). Figure 5 C, D). After 14 days of incubation, the expression of Sox9 was upregulated by 12.39-fold and 9.56-fold in the CMA-Mg group and the CMA group, respectively; the expression of Col2a1 gene was upregulated by 28.60-fold and 8.95-fold in the CMA-Mg group and the CMA group, respectively. These results indicate that CMA-Mg hydrogel has excellent biological activity and significantly promotes the differentiation of BMSCs.

[0064] Example 7 3D printed collagen bioscaffold promotes skin wound healing

[0065] By constructing a full-thickness skin defect model in SD rats, we evaluated the ability of 3D collagen bioscaffolds to promote the repair of full-thickness skin defects in vivo ( Figure 6 ). CMA and CMA-Mg scaffolds with a diameter of 13 mm and a height of 3 mm were printed and implanted into skin defects with a diameter of 13 mm. The control group was an untreated skin defect. The effect of the scaffold material on skin defect repair was evaluated 7, 14, and 21 days after implantation.

[0066] The wound healing of rats was evaluated on the 7th, 14th and 21st days of treatment. Figure 6 ). On the 7th day after treatment, wound healing photos showed that the wound healing effect of CMA-Mg and CMA hydrogel groups was better than that of the control group. The wound healing rates of CMA-Mg and CMA hydrogel groups were approximately 21.84% and 18.90%, while the wound healing rate of the blank group was only 11.81%. On the 14th day, the wound area of ​​the CMA-Mg hydrogel group was the smallest, and the wound closure rate was 87.11%. The wound closure rates of the blank group and CMA group were 58.65% and 79.96%, respectively. After 21 days of treatment, the wounds in the CMA-Mg hydrogel group were almost completely healed, and the color was consistent with the adjacent skin tissue. There were still unhealed wounds in the blank group; there were small wound remnants in the CMA group, and scar tissue appeared; the wound healing rates of the blank group and CMA group were 84.96% and 93.16%, respectively. The results showed that CMA-Mg hydrogel has the ability to significantly promote the repair of full-thickness skin injuries in rats.

[0067] To evaluate the effect of collagen hydrogel scaffolds on the repair of full-thickness skin defects, we performed histological analysis ( Figure 7 H&E staining was used to evaluate the granulation tissue formation and epidermal regeneration in the full-thickness skin defect model of SD rats at different time points ( Figure 7 A, C, D). Granulation tissue is formed by the activity of fibroblasts, matrix remodeling, and growth factors and is a key indicator of wound healing. The thicker the granulation tissue, the faster the wound heals. After 7 days of treatment, the granulation tissue increased in both the CMA-Mg and CMA groups; 14 days after surgery, the regeneration of granulation tissue in both the CMA-Mg and CMA groups was significantly reduced ( Figure 7 C). During the treatment period, epidermal regeneration in the CMA-Mg and CMA groups was significantly higher than that in the blank group ( Figure 7 D). These results indicate that the wound healing in the CMA-Mg group was more complete, with significant re-epithelialization, granulation tissue formation, and new skin attachment formation.

[0068] Masson trichrome staining was used to evaluate the collagen deposition in the wound regeneration area. Figure 7B, E). Collagen deposition has multiple important functions in wound healing, including providing mechanical support for newly formed tissues, promoting cell proliferation and differentiation, and promoting the overall healing process. On the 7th day, new collagen fibers were formed in the skin defect sites of the blank group, CMA group, and CMA-Mg group, accounting for 8.96%, 19.89%, and 28.83%, respectively. On the 14th day, the number of collagen fibers in each group increased to 23.38%, 46.70%, and 50.23%, respectively. After 21 days of treatment, CMA-Mg and CMA regenerated a large number of dense collagen fibers, accounting for 81.63% and 79.21%, respectively, while the regenerated collagen fibers in the blank group were sparsely distributed, with a content of only 43.56%. Masson staining results showed that the collagen deposition in the CMA-Mg group was the thickest, densest, and most evenly arranged. In summary, the results of H&E and Masson staining consistently showed that CMA-Mg hydrogel can effectively promote skin tissue repair.

[0069] In summary, the present invention provides a Mg 2+ DLP 3D printing bio-ink for collagen, the bio-ink comprising the following components: 0.5% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ solution; the bio-ink has good fluidity and can be quickly solidified under blue light irradiation to achieve DLP 3D precision printing of CMA; the 3D printed scaffold has high mechanical strength and strong resistance to enzyme degradation; the 3D collagen bio-scaffold has high biocompatibility and bioactivity, and significantly promotes cell proliferation, migration and differentiation; the 3D printed bio-scaffold can promote the orderly deposition of collagen and accelerate epidermal regeneration; 3D printed bio-scaffolds are widely used in the fields of skin repair and bone and cartilage repair tissue engineering.

Claims

1. A kind of Mg 2+ DLP 3D printing bio-ink for collagen, characterized in that The bio-ink comprises the following components: 0.1% to 1% m / v methacrylated collagen solution, 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ Solution.

2. The bio-ink according to claim 1, characterized in that: The collagen is yak collagen.

3. The bio-ink according to claim 2, characterized in that: The yak collagen is type I yak collagen, and / or type II yak collagen, and / or type Ш yak collagen.

4. The bio-ink according to claim 1, characterized in that: The photoinitiator includes one or more of LAP, TPO and I2959.

5. The bio-ink according to claim 1, characterized in that: The ultraviolet absorber includes one or more of lemon yellow and food coloring brilliant blue.

6. The method for preparing the biological ink according to any one of claims 1 to 5, characterized in that: The steps include: (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve; (2) adding sodium hydroxide solution to adjust the pH of the collagen solution obtained in step (1) to 7-9, and then adding methacrylic anhydride dropwise to maintain the pH of the solution at 7-8; reacting in an ice bath for 24 hours, dialyzing in ultrapure water, and freeze-drying to obtain methacrylated collagen; (3) Prepare 0.5% to 1% m / v methacrylated collagen solution with 0.5M acetic acid solution, add 6M sodium hydroxide solution to adjust the pH of the solution to neutral, add 0.1% to 0.5% m / v photoinitiator, 0.1% to 0.5% m / v UV absorber and 0.1% to 0.5% m / v Mg 2+ The solution was mixed evenly and centrifuged to remove bubbles to obtain CMA-Mg 2+ Bio-ink.

7. The method for preparing biological ink according to claim 1, characterized in that: The amount of methacrylic anhydride added in step (2) is ten times the equivalent of collagen lysine.

8. A method for preparing a 3D printing functional active material, characterized in that: include: The bio-ink is added to a 3D bio-printer for printing, and then photo-crosslinked to obtain a 3D printing functional active material, wherein the bio-ink is the bio-ink described in any one of claims 1 to 5 or the bio-ink prepared by the preparation method described in any one of claims 6 to 7.

9. A 3D printing functional active material, obtained by sequentially subjecting the bio-ink described in any one of claims 1 to 5 or the bio-ink prepared by the preparation method described in any one of claims 6 to 7 to 3D printing and cross-linking treatment.

10. Use of the 3D printing functional active material according to claim 9 in the preparation of skin repair materials, bone and cartilage repair materials, and tissue engineering.

Citation Information

Patent Citations

  • 3D printing bio-ink and preparation method thereof, 3D printing living body functional material and preparation method and application thereof

    CN116212109A